NILAI-NILAI AJARAN ISLAM DALAM PAKET WAYANG SYADAT DI SINGOSARI MALANG - Abdurrahman; Amatul Jadidah (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2020)
In this study, researchers wanted to know the purpose of forming wayang shadat in Gentong hamlet as a media approach to socialize Islamic teachings and the effectiveness of wayang shadat in transforming Islamic teachings to the Gentong hamlet community. This research was conducted in Gentong-Purwoasri Hamlet, Singosari District, Malang Regency. In collecting this data the researcher used the method of observation, interviews, documentaries, questionnaires, and data analysis with percentages. The population taken in the study was the entire Gentong hamlet community of 200 people, while the researchers only took 40 people (20%) to be used as a sample consisting of community leaders, hamlet officials, parents and youth. From the results of this study, data can be obtained that the purpose of forming Wayang Syadat is to socialize Islamic teachings and regarding the transformation of Islamic values through Wayang Syadat performances, which can be said to be very effective. Because this approach is in accordance with the background of the Gentong hamlet community, most of whom really like gamelan-smelling art.